Rancang Bangun Aplikasi Data Pasien Rumah Sakit Berbasis Android dan MySQL - Dharma, Aditya Guna; Ardiansyah, Alwi (Himpunan Dosen Gemilang Indonesia (HDGI), 2023)
When the author conducted research on patient data at the hospital, the author found that so far to obtain patient information it still took a long time. This is because patient data storage has not used a database. To support technology in the era of globalization, the author makes an Android-based hospital patient data application. This Student Data Application aims to make it easier for staff and employees at the hospital to quickly record patient data. This application is built with Java Android programming using the ADT Bundle Android Studio software in which there is a database as a programming language editor. While the database used is MySQL. The application development methodology that I use is the Waterfall methodology. This Waterfall methodology has several stages, namely Analysis, System Design, Implementation, Integration, Operation and Maintenance. In the process of collecting data the author uses the method of observation and interviews. While in making the application, the tool used in making the design and design of the Hospital Patient Data Application is by using the Unified Modeling Songage (UML). The final result of this research is a patient data application based on Android. This application has several main features such as data input, displaying a list of stored data, editing data and deleting stored data.